Sunnah foods for the treatment of infertility in women with PCOS: a literature review - Ya’u, Dahira Sani; Abdul Hamid, Habibah; MD Pauz, Siti Farhana; Sulaiman, Norhasmah (Universiti Putra Malaysia Press, 2024)
Infertility is a global health issue that is on the rise. The leading cause of female infertility, PCOS, is considered incurable and lifelong in conventional medicine. Challenging and delayed diagnosis, ineffective treatment modalities and long-term treatment has left both physicians and patients disgruntled. Islamically however, it is believed that every illness has a cure. This paper is therefore aimed at reviewing the effect of Sunnah foods in treating infertility among patients with PCOS. The study will also provide future recommendation for researchers and practitioners.